Anti-osteoporosis treatments changed body composition in postmenopausal women: A systematic review and meta-analysis. Issue 36 (9th September 2022) - Shi, Lingfeng; Xu, Xiaoli; Xiang, Guangda; Duan, Shanshan
Abstract : Background: Whether the widespread anti-osteoporosis treatments in postmenopausal women also benefit the change of body composition (lean body mass [LBM] and body fat mass [FM]) remains controversial. In order to solve this issue and find out the most effective treatment, we conducted this meta-analysis. Methods: We searched the literature, via PubMed, Embase, Scopus, Web of Science, and Cochrane to screen citations from inception to March 26, 2022, for inclusion in this study. Only clinical trials that used anti-osteoporosis treatments in postmenopausal women and displayed the alteration of body composition were included. Stata 14.0 was used for the meta-analysis. Results: Our meta-analysis results presented that: compared with placebo, hormone replacement therapy (HRT) was associated with increased LBM (standardized mean differences [SMD] = 0.32, 95% confidence interval [CI] = 0.02–0.61) and reduced FM (SMD = −0.30, 95% CI = −0.51 to −0.09) in postmenopausal women. Compared with placebo, physical exercise training showed an effect of decreasing FM (SMD = −0.66, 95% CI = −0.94 to −0.38) but not significant influence LBM (SMD = 1.31, 95% CI = −0.29 to 2.91). The network meta-analysis of our study showed that oral estrogen and progestogen plus exercise (OEPE) treatment might be the most effective anti-osteoporosis treatment (surface under the cumulative ranking curve 99.9) to reduce FM in postmenopausal women. Conclusions: anti-osteoporosis treatments, especially HRT, affect body composition. Furthermore, the combination of HRT and exercise training are the most effective treatment to reduce FM while maintaining LBM.